HUBUNGAN INDEKS MASSA TUBUH (IMT) DAN LINGKAR PINGGANG DENGAN HIPERTENSI PADA MASYARAKAT DESA MESJID SUNGAI IYU - Bunga Theresia Purba; Normi Parida Sipayung; Henny Syapitri (Jurnal Reproductive Health, 2019)
Hypertension is often referred as a dark killer (silent killer), because it includes a deadly disease without any prior symptoms as a warning to the victim. Obesity is one of the factors that increase the risk of hypertension and heart attack. One method to prevent hypertension is to keep the weight off. Some anthropometric measurements conducted to identify obesity as screening for cardiovascular disease, one of which is through the measurement of BMI and waist circumference. This study aims to determine the relation of BMI and waist circumference with hypertension in village communities at Masjid SungaiIyu Aceh Tamiang. This research is a correlation Analytical study with cross sectional design. The sample in this research that most people who live in the village of Masjid Sungai IyuAceh Tamiang thataged 25-55 years amounted to 73 people, the sampling is purposive sampling technique. Results of statistical test Spearman correlation between BMI with systolic and diastolic blood pressure was obtained p value = 0.000 (p value <0.05). It is known that there is a significant relation between BMI and waist circumference with systolic and diastolic blood pressure and closeness of this relationship has a strong, positive patterned. It is recommended to the public to perform routine measurements of BMI and waist circumference. People who have BMI and waist circumference above the normal recommended to exercise regularly, reduce the consumption of fatty foods and more activity in order to prevent accumulation of abdominal fat area which could be at risk of hypertension.